Methodology of Development of Coaching Competence in Female Wrestlers (Global Scientific Review, 2023)
This article presents a comprehensive methodology for the development of coaching competence specifically tailored for female wrestlers. With the growing prominence of women's wrestling, there is an increasing need for effective coaching strategies that consider the unique physiological, psychological, and sociocultural aspects of female athletes. The proposed methodology integrates theoretical foundations of coaching, gender-specific considerations, and practical training techniques. Drawing on insights from sports science, psychology, and pedagogy, the methodology encompasses both technical coaching skills and the cultivation of a supportive and empowering coaching environment. By addressing the distinctive needs of female wrestlers, this methodology aims to enhance coaching effectiveness, foster athlete development, and contribute to the overall growth and success of women's wrestling